1994
DOI: 10.1002/elps.11501501118
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomer separation using mobile and immobile cyclodextrin derivatives with electromigration

Abstract: The principle of electrochromatography is applied to enantiomer separation with wall-coated capillaries of 50 microns (ID). As chiral stationary phase an immobilized polysiloxane containing chemically bonded monokis-6-O-octamethylene-permethyl-cyclodextrin (beta- or gamma-Chirasil-Dex) was used. The results are compared with the conventional method of adding cyclodextrin derivatives as chiral pseudostationary phase to the running buffer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(38 citation statements)
references
References 15 publications
0
38
0
Order By: Relevance
“…Pioneering work in CEC has been done by Schurig's group [491,492]. Permethylated b-cyclodextrin was attached via an octamethylene spacer to a dimethylpolysiloxane and coated on the capillary wall (Chirasil-Dex).…”
Section: Open Tubular Capillariesmentioning
confidence: 99%
“…Pioneering work in CEC has been done by Schurig's group [491,492]. Permethylated b-cyclodextrin was attached via an octamethylene spacer to a dimethylpolysiloxane and coated on the capillary wall (Chirasil-Dex).…”
Section: Open Tubular Capillariesmentioning
confidence: 99%
“…Not only neutral cyclodextrins [3 -5], but also charged cyclodextrins [6] (e.g. sulfobutyl ether b-CD [7,8], carboxymethyl b-CD [9], ...) and cyclodextrins imprinted in polymers [10,11] or in coatings [12,13] have been used. Some reports discuss the applicability of dual-cyclodextrin systems, in which charged and uncharged cyclodextrins are mixed [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the optimization of the analytical wavelength value, the reference wavelength, and the bandwidth (it will be indicated within parentheses) of those wavelengths was performed. Preliminary studies were carried out at an analytical wavelength of 230 nm (4) [18,25] with the lowest possible bandwidth and without reference wavelength. From the absorption spectrum of etodolac it was observed that the absorption band of maximum absorption is around 230 nm.…”
Section: Methods Optimizationmentioning
confidence: 99%